Biases in the Criminal Justice System with Reference to the Practice of Compulsory Treatment of Mentally Ill Offenders - Gula, Krisztina Petra (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
One of the least researched areas of the economic analysis of law today is Criminal law and Criminal justice. A contemporary line of thinking and examination is the behavioural economic approach that reflects on various mental distortions (i.e. biases) affecting the decision-making and situationassessment of individuals. The focus of my essay is the intersection of Criminal law and behavioural economics in the sphere of biases influencing the participants in criminal proceedings. The measure of compulsory treatment in the cases of mentally ill offenders serves as an illustration: the application of the sanction, as well as the review procedure aimed at deciding whether an already applied sanction could be ceased and the treated person should be released. Outlining this measure is justified by the fact that the potential considerations and evaluations of mentally ill offenders cannot be taken into account as those of sane perpetrators (who are in no state of impairment of the mind). This places an even greater responsibility on the rest of the procedural participants – especially judges and experts – to deliver well-reasoned decisions by eliminating the eventual negative consequences of their generally less reflected mental distortions that could pose further detriments to the mentally ill. As a closure, I am referring to certain ways and means that can potentially reduce the role of biases in the criminal proceedings and thus contribute to fairer jurisdiction for the mentally ill.